Interior Rumah Makan Lesehan dan Kolam Pancing Agung di Malang - Tanudjaja, Chyntia (Intra, 2014)
This project intends to design the interiors of the branch of Rumah Makan Lesehan dan Kolam Pancing Agung that will be located in the city of Batu, Malang. The objectives that is hoped to be achieved are to give ergonomic and comfortable feeling, and also to accentuate the Javanese local contents. By applying exotic, unique and authentic concepts, and also traditional contemporary styles, the objective of making Rumah Makan dan Kolam Pancing Agung as a well-known tourist destination can hopefully be achieved.